Inflammation, but not recruitment, of adipose tissue macrophages requires signalling through Mac-1 (CD11b/CD18) in diet-induced obesity (DIO) (Thrombosis and Haemostasis, 2017)
Cell accumulation is a prerequisite for adipose tissue inflammation. The leukocyte integrin Mac-1 (CD11b/CD18, αMβ2) is a classic adhesion receptor critically regulating inflammatory cell recruitment. Here, we tested the hypothesis that a genetic deficiency and a therapeutic modulation of Mac-1 regulate adipose tissue inflammation in a mouse model of diet-induced obesity (DIO). C57Bl6/J mice genetically deficient (Mac-1-/-) or competent for Mac-1 (WT) consumed a high fat diet for 20 weeks. Surprisingly, Mac-1-/- mice presented with increased diet-induced weight gain, decreased insulin sensitivity in skeletal muscle and in the liver in insulin-clamps, insulin secretion deficiency and elevated glucose levels in fasting animals, and dyslipidaemia. Unexpectedly, accumulation of adipose tissue macrophages (ATMs) was unaffected, while gene expression indicated less inflamed adipose tissue and macrophages in Mac-1-/- mice. In contrast, inflammatory gene expression at distant locations, such as in skeletal muscle, was not changed. Treatment of ATMs with an agonistic anti-Mac-1 antibody, M1/70, induced pro-inflammatory genes in cell culture. In vivo, treatment with M1/70 induced a hyper-inflammatory phenotype with increased expression of IL-6 and MCP-1, whereas accumulation of ATMs did not change. Finally, inhibition of Mac-1’s adhesive interaction to CD40L by the peptide inhibitor cM7 did not affect myeloid cell accumulation in adipose tissue. We present the surprising finding that adhesive properties of the leukocyte integrin Mac-1 are not required for macrophage accumulation in adipose tissue. Instead, Mac-1 modulates inflammatory gene expression in macrophages. These findings question the net effect of integrin blockade in cardio-metabolic disease.D. W., N. B., and D. E. equally contributed to this work.K. P., E. L., and A. Z. share senior authorship.Note: The review process for this manuscript was fully handled by Gregory Y. H. Lip, Editor in Chief.Supplementary Material to this article is available online at www.thrombosis-online.com.
Keywords: Obesity; metabolic disorders; inflammation; macrophage; adhesion molecules